The Concept of Law in Economic Science - Kaufmann, Felix (Review of Economic Studies, 1934)
Journal Article The Concept of Law in Economic Science Get access Felix Kaufmann Felix Kaufmann Vienna Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 2, February 1934, Pages 102–109, https://doi.org/10.2307/2967616 Published: 01 February 1934